Factors affecting provision of female family planning commodities in public health facilities in Kajiado county, Kenya - Fredrick Githinji; Shital M. Maru; Peter N. Karimi; Eugene Rutungwa; Egide Kayitare (Taylor & Francis Group, 2022)
Background Family planning involves the use of traditional or modern methods to prevent maternal and infant mortality associated with unintended pregnancies and negative economic outcomes. In sub-Saharan Africa, the unmet need for modern family planning is approximately 66%. However, information on factors affecting utilization of female family planning commodities is limited. Therefore, this research was conducted to bridge this gap. Methods Health facility-based descriptive cross-sectional research design was conducted and involved the public health facilities offering family planning, targeting respondents who handle the commodities and service providers themselves. A semi-structured questionnaire was used to collect data about availability of the commodities, knowledge of service providers and barriers affecting provision of the service. Data were coded and analyzed via Microsoft Excel 2019 and SPSS version 20. Results The study showed that shorter term methods were more readily available, 60-75% than the long-term methods, 20-60%. Approximately 60% of the service providers did not comprehensively utilize the recommended World Health Organization Medicine Eligibility Criteria (WHO MEC) during service provision. Stock outs, myths and misconceptions, male interference and culture were the major barriers identified. Conclusion Provision of family planning commodities in public health facilities in Kajiado county is affected by stock levels at the national program, and provider knowledge on WHO MEC. The key factors affecting provision of family planning were stock outs, myths and misconceptions on the contraceptives, inadequate male involvement and inadequate community engagement on potential benefits of the service. These challenges need to be part of the solutions to bridging the gap identified.